2015
DOI: 10.1002/prp2.171
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 (Fingolimod) sensitizes hepatocellular carcinoma cells to sorafenib‐mediated cytotoxicity

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide. The multityrosine kinase inhibitor sorafenib is used in the therapy of advanced disease. However, the effects of sorafenib are limited, and combination treatments aiming at improved survival are encouraged. The sphingosine analog FTY720 (Fingolimod), which is approved for treatment of multiple sclerosis, has shown tumor suppressive effects in cell lines and animal models of HCC. In the present study, we combined sora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Anti‐S1P monoclonal antibodies that specifically neutralize and target S1P are effective against breast, lung, or ovarian cancer cells, melanoma cells, and renal cancer models in vivo, while SphK inhibition has been shown to reduce the viability of glioblastoma multiforme cells, neuroblastoma cells, several types of leukemia cells, and various solid tumor cell lines . The selective SphK1 inhibitor FTY720, which has cytotoxic effects in various cancers, induces apoptosis in cell lines and animal models of HCC and sensitizes HCC cells to sorafenib‐mediated cytotoxicity . Another SphK inhibitor, N,N ‐dimethylsphingosine (DMS) is known to suppress proliferation and migration of HCC cells .…”
Section: Discussionmentioning
confidence: 99%
“…Anti‐S1P monoclonal antibodies that specifically neutralize and target S1P are effective against breast, lung, or ovarian cancer cells, melanoma cells, and renal cancer models in vivo, while SphK inhibition has been shown to reduce the viability of glioblastoma multiforme cells, neuroblastoma cells, several types of leukemia cells, and various solid tumor cell lines . The selective SphK1 inhibitor FTY720, which has cytotoxic effects in various cancers, induces apoptosis in cell lines and animal models of HCC and sensitizes HCC cells to sorafenib‐mediated cytotoxicity . Another SphK inhibitor, N,N ‐dimethylsphingosine (DMS) is known to suppress proliferation and migration of HCC cells .…”
Section: Discussionmentioning
confidence: 99%
“…10 Recently, FTY720 was found to inhibit the growth of various tumors, including HCC tumors. 40,41 Because of its nontoxicity, specific cytotoxicity toward tumors and high oral bioavailability, FTY720 has great potential for tumor therapy. However, after exploring the use of FTY720 in various cancers, studies have shown that this drug substantially induces autophagy in tumor cells, which protects them from damage and reduces apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the anticancer mechanism of FTY720 involves inhibition of the proto-oncogene sphingosine kinase 1; however, the anticancer properties of FTY720 may be attributable to its effects on several other molecular targets (24,25). Furthermore, FTY720 was reported to modulate autophagy; a number of studies have reported the induction of autophagy by FTY720 (26)(27)(28)(29), while others have reported autophagy suppression (30)(31)(32)(33). Autophagy exhibits complex, context-dependent properties in cancer, and interventions that stimulate or inhibit autophagy have been proposed as potential anti-cancer therapies (34).…”
Section: Introductionmentioning
confidence: 99%